2021
DOI: 10.3389/fimmu.2021.786046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Age on Clinical Efficacy and Toxicity of Checkpoint Inhibitor Therapy

Abstract: The addition of immune checkpoint inhibitors (ICIs) to the therapeutic armamentarium for solid malignancies has resulted in unprecedented improvements in patient outcomes in many cancers. The landscape of ICIs continues to evolve with novel approaches such as dual immune checkpoint blockade and combination therapies with other anticancer agents including cytotoxic chemotherapies and/or antiangiogenics. However, there is significant heterogeneity seen in antitumor responses, with certain patients deriving durab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 86 publications
(74 reference statements)
0
26
0
Order By: Relevance
“…In this study, patients younger than 60 years had a higher risk of pneumonitis. A recently published review discussed the complex relationship between age and irAEs ( 73 ). The results varied with the age cut-off chosen (worse in ≥ 65 years vs < 65 years, worse in a median age group of 70 years vs. 62 years).…”
Section: Patient-specific Risk Factors For Iraementioning
confidence: 99%
“…In this study, patients younger than 60 years had a higher risk of pneumonitis. A recently published review discussed the complex relationship between age and irAEs ( 73 ). The results varied with the age cut-off chosen (worse in ≥ 65 years vs < 65 years, worse in a median age group of 70 years vs. 62 years).…”
Section: Patient-specific Risk Factors For Iraementioning
confidence: 99%
“…Compared with older patients, ‘reproductive system and breast disorders’ were the main irAEs caused by ICIs in patients aged 18–64. Age-related changes in the immune system may affect the efficacy and toxicity of ICI drugs [ 51 , 54 ]. Here we demonstrate that patients of age 65–85 are more susceptible to ICI-related renal and urologic toxicity, while those of age 18–64 have more reproductive toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers anticipate the development of additional therapies to tackle checkpoint components would enhance the clinical results for patients and eventually lead to cancer eradication [ 24 , 25 , 31 ]. The majority of findings for elderly and ccRCC patients, whether in localized or distant areas during the ICI and non-ICI era, are still in their early stages [ 32 , 33 , 34 ]. In the clinical context of RCC aging, several reports revealed that the prognosis for individuals over 65 years old with RCC is significantly worse than for those under 65 years [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%